Enhanced Relationship between Central Tropical Pacific Sea Surface Temperature and Eurasian Surface Air Temperature during Boreal Summers - Ming, Jing; Sun, Jianqi (Journal of climate, 2021)
This study investigates the relationship between the central tropical Pacific (CTP) sea surface temperature (SST) and the surface air temperature (SAT) variability unrelated to canonical El Niño–Southern Oscillation (ENSO) over mid–high-latitude Eurasia during boreal summers over the past half-century. The results show that their relationship experienced a decadal shift around the early 1980s. Before the early 1980s, the Eurasian SAT–CTP SST connection was weak; after that time, the relationship became stronger, and the SAT anomalies exhibited a significant wavelike pattern over Eurasia. Such a decadal change in the Eurasian SAT–CTP SST relationship could be attributed to decadal changes in the mean state and variability of CTP SST. The warmer mean state and enhanced SST variability after the early 1980s reinforced the convective activities over the tropical Pacific, leading to significantly anomalous divergence/convergence and Rossby wave sources over the North Pacific. This outcome further excited the wave train propagating along the Northern Hemisphere zonal jet stream to northern Eurasia and then affected the surface heat fluxes and atmospheric circulations over the region, resulting in wavelike SATs over Eurasia. However, during the period before the early 1980s, the CTP SST had a weak impact on the North Pacific atmospheric circulation and was consequently not able to excite the wave train pattern to impact the Eurasian atmospheric circulation and SATs. The physical processes linking the CTP SST and Eurasian SAT are further confirmed by numerical simulations. The results of this study are valuable to understanding the variability of summer Eurasian SATs.